The Use of Peer Mediation and Educator Facilitation to Promote Turn Taking in Young Children With Autism Spectrum Disorder in Inclusive Childcare. Issue 3 (July 2019) - Kemp, Coral; Stephenson, Jennifer; Cooper, Megan; Hodge, Kerry
Abstract : A multiple-probe design across participants was used to investigate the effect of a peer-mediated intervention on the turn-taking behavior of 3 children with autism spectrum disorder (ASD) attending inclusive childcare centers. An educator trained peers to support the child with a disability to take turns playing a game on an iPad. The educator was also available to provide coaching for the peer when needed. An intervention effect was demonstrated for each of the children, and 2 were able to demonstrate maintenance of the skill when the training and coaching procedures were not implemented by the educator. Although some elements of the treatment procedures were not consistently applied by the educators or typical peers, the intervention was sufficiently robust to enable the children with ASD to improve their turn-taking skills.